TANGGUNG JAWAB HUKUM PEMERINTAH DALAM PENYELENGGARAAN PENDIDIKAN NASIONAL - Franciscus Xaverius Wartoyo (Faculty of Law, Universitas Sebelas Maret, 2016)
AbstractGovernment has the legal responsibilities in the implementation of national education system to carry out the mandate set out in Section 31 of the Constitution of the Republic of Indonesia 1945 related to the intellectual life of the nation. This is confirmed and applied by The Indonesian Government Regulation 47/2008 regarding compulsory education and Indonesian Government Regulations 48/2008 related to the funding education of elementary school (SD) to high school (SMP) free made by the government through the School Operational Assistance (BOS) to make the education system based on the national human values and justice according to Pancasila ad realize the human rights set out in the Constitution Indonesian 1945 Article28 c paragraph(1) and Article 28d paragraph (3) stated that every citizen has the right to obtain equal opportunities in government. The free primary education can not be realized in a fair and equitable for the presence of education autonomy, every area is not the same policies and management education in many schools that are not transparent even still many schools to collect funds for the reason given by the government budget for operational costs is not enough.In addition, the9-year basic education which should be free up to secondary education (high school) born by either the state of infrastructure, teachers’ salaries, electricity, telephone, computer, books, stationery without distinguishing between public and private schools. AbstrakPemerintah memiliki tanggung jawab hukum dalam implementasi sistem pendidikan nasional sebagai amanah (mandat) dari Pasal 31 Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 yakni hak mendapatkan pendidikan yang layak. Mandat tersebut diturunkan dalam Peraturan Pemerintah Nomor 47 Tahun 2008 tentang wajib belajar dan Peraturan Pemerintah Nomor 48/2008 tentang Pendanaan Pendidikan dari Sekolah Dasar ( SD ) hingga Sekolah Menengah ( SMP ) yang gratis ditanggung oleh pemerintah melalui Bantuan Operasional Sekolah ( BOS ) dalam rangka untuk menciptakan sistem pendidikan berdasarkan pada nilai-nilai kemanusiaan nasional dan keadilan dalam Pancasila, serta dalam rangka penegakan Hak Asasi Manusia berdasar Pasal 28C ayat (1) dan Pasal 28D ayat (3) dimana setiap warga negara memiliki kesempatan yang sama dalam pemerintahan. Pendidikan dasar gratis tidak dapat dicapai secara adil dan merata karena setiap daerah miliki kebijakan dan manajemen pendidikan yang berbeda, adanya ketidaktransparanan sekolah dalam mengelola dana, dan faktor alasan ketidakcukupan dana yang diberikan oleh pemerintah kepada sekolah. Pendidikan Dasar 9 (sembilan tahun) seharusnya gratis sampai pada Pendidikan Menengah Pertama (SMP) baik dalam hal infrastruktur pendidikan, honor guru, biaya listrik, telepon, pengadaan komputer, buku-buku tanpa ada pembedaan sekolah publik dan sekolah swasta.